Evaluation of EU Risk assessment existing chemicals (EC Regulation 793/93) - Berthault, Francis; Pronk, M.E.J.; Vermeire, T.G.; Bodar, Charles W.M. (Bilthoven, 2002)
An evaluation was performed on the first group (41) of completed risk assessments for chemicals of the EU priority lists (Existing Chemicals; EC Regulation 793/93). The evaluation focussed on the conclusions of the risk assessments. The EU risk assessment process detected a high number of substances of concern. Furthermore priority chemicals may pose (potential) risks to the whole range of protection goals of the risk assessment. The predictability of the risk assessments for priority chemicals was investigated. Our a priori knowledge on possible risks of priority chemicals is found to be poor, especially for consumers. Both for environment and human health the (potential) risks were linked with a broad spectrum of use patterns. It is concluded that no industry category can in advance be excluded from performing risk assessments. For a great number of chemicals, additional testing was found to be needed to finalise the risk assessment. This evokes questions about the completeness of the current base-set, but also about the suitability of some of the submitted human health tests that should initially fulfil the base-set needs. The results of this evaluation are useful for future discussions on risk assessment processes for chemicals.